Polygyny Amongst Muslims in the Russian Federation - Kończak, Izabela (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
Polygynous families had been living legally in Russia in the areas inhabited by Muslims from the October Revolution to the mid-twentieth century. However, such a family model was not common among the followers of Islam. An act penalizing bigamy or polygamy was introduced into the Penal Code in 1960. During perestroika, and later changes in the political system, imams who came from abroad began to visit areas inhabited by Muslims. They contributed to the rebirth of religion and promoted the idea of polygamy. Polygyny is the visible sign of dissimilarity and Muslim identity and was an important point in their teaching. In this context the number of polygynous relationships in Russia has increased significantly. The article is dedicated to the analysis of social and political discourse in Russia that has been taking place for several years.